Gut Epithelial Metabolism as a Key Driver of Intestinal Dysbiosis Associated with Noncommunicable Diseases - Shelton, Catherine D. (Infect Immun, 2020)
In high-income countries, the leading causes of death are noncommunicable diseases (NCDs), such as obesity, cancer, and cardiovascular disease. An important feature of most NCDs is inflammation-induced gut dysbiosis characterized by a shift in the microbial community structure from obligate to facultative anaerobes such as Proteobacteria. This microbial imbalance can contribute to disease pathogenesis by either a depletion in or the production of microbiota-derived metabolites. However, little is known about the mechanism by which inflammation-mediated changes in host physiology disrupt the microbial ecosystem in our large intestine leading to disease. Recent work by our group suggests that during gut homeostasis, epithelial hypoxia derived from peroxisome proliferator-activated receptor γ (PPAR-γ)-dependent β-oxidation of microbiota-derived short-chain fatty acids limits oxygen availability in the colon, thereby maintaining a balanced microbial community. During inflammation, disruption in gut anaerobiosis drives expansion of facultative anaerobic Enterobacteriaceae, regardless of their pathogenic potential. Therefore, our research group is currently exploring the concept that dysbiosis-associated expansion of Enterobacteriaceae can be viewed as a microbial signature of epithelial dysfunction and may play a greater role in different models of NCDs, including diet-induced obesity, atherosclerosis, and inflammation-associated colorectal cancer.